2019
DOI: 10.3390/nano9030420
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated Salt/Graphite/Polyelectrolyte Organic-Inorganic Hybrids for Efficient Thermochemical Storage

Abstract: Hydrated salt thermochemical energy storage (TES) is a promising technology for high density energy storage, in principle opening the way for applications in seasonal storage. However, severe limitations are affecting large scale applications, related to their poor thermal and mechanical stability on hydration/dehydration cycling. In this paper, we report the preparation and characterization of composite materials manufactured with a wet impregnation method using strontium bromide hexahydrate (SBH) as a thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It is generally classified as a sorption process or a chemical reaction that does not involve sorption. However, compared to liquid absorption and solid adsorption, chemical reactions are mono-variant and lead to transformation about the volume of the solid [129][130][131][132][133]. The main chemical reaction storage materials developed and studied can be grouped into carbonate decomposition material, redox material, inorganic hydroxide material, ammonia decomposition material, metal hydride material, and methane reforming material.…”
Section: Materials For Chemical Reaction Energy Storage Processmentioning
confidence: 99%
“…It is generally classified as a sorption process or a chemical reaction that does not involve sorption. However, compared to liquid absorption and solid adsorption, chemical reactions are mono-variant and lead to transformation about the volume of the solid [129][130][131][132][133]. The main chemical reaction storage materials developed and studied can be grouped into carbonate decomposition material, redox material, inorganic hydroxide material, ammonia decomposition material, metal hydride material, and methane reforming material.…”
Section: Materials For Chemical Reaction Energy Storage Processmentioning
confidence: 99%
“…Such a behaviour is ascribed to the limitations in mass transfer since composites with higher content of salt results in more compact and dense blocks, that represent increased obstacles to mass and heat transfer. In the work reported by Salviati et al [23], the composites made with the salt hydrate, expanded natural graphite and polydiallyldimethylammonium chloride show good heat and mass transfer properties, but the mechanical resistance of the material proved to be a critical issue: severe damage in the form of cracks to the composite tabs occurred already after the first hydration/dehydration cycle. In another study by D'Ans et al [39], a strong humidity dependence of thermal and mass transport properties of composites based on CaCl2 encapsulated in microporous silica gel was evidenced: considering the small dimensions of the pores of the matrix, for high humidity values (i.e.…”
Section: Feasibility Of the Composites For Thermal Energy Storage Application And Future Developmentsmentioning
confidence: 99%
“…The results showed that the natural graphite could improve the hydration-dehydration kinetics by reducing hysteresis and increase the thermal conductivity of the material. More recently, Salviati et al [23] proposed the addition of an organic compound, PDAC, polydiallyldimethylammonium chloride, to the strontium bromide/graphite composites. Experimental outcomes of the investigation show that PDAC has a beneficial effect on water sorption and mechanical resistance upon hydration/dehydration cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Mm-size particles are typically obtained by various methods from μmsize powders [10,[13][14][15][16][17]. There have been multiple attempts to make mm-size composite particles, with the aim to conjugate a newly achieved mechanical stability with additional functionalities in support of mass and heat transfer.…”
Section: Introductionmentioning
confidence: 99%